Research on healing-oriented street design based on quantitative emotional electroencephalography and eye-tracking technology - Shao, Huibin; Liu, Ying; Ren, Hongguo; Li, Zhenyu (Frontiers in Human Neuroscience, 2025)
This study seeks to evaluate how street space design impacts users’ psychological healing. In the introduction, we highlight the significance of this research area and outline our objectives. Regarding methods, we employed Electroencephalography (EEG) and eye - tracking technologies, centering on two design elements: street interface type and green ratings, and used physiological indicators to measure users’ healing responses. As for results, EEG data showed that open space interfaces reduce cognitive load while high green ratings offer positive natural stimulation, both enhancing healing effects. Eye - tracking data indicated that green ratings might influence healing more than interface type, likely due to their role in determining natural element richness. The subjective questionnaire also underlined the importance of being away and extent in street healing. In the discussion, we confirm the effectiveness of EEG and eye - tracking in assessing street space healing and present an evaluation framework blending physiological and emotional responses. Overall, this study provides an empirical basis for optimizing street space design and improving design interventions.